The Impact Of Corona Virus On Share Prices In All Company Sectors In The Indonesia Stock Exchange - An Suci Azzahra; Ayu Wirdha Ningsih (Enrichment : Journal of Management, 2021)
The purpose of this study is to analyze the impact of the corona virus on stock prices in all company sectors on the Indonesia Stock Exchange. This study examines whether there are differences in stock prices before and after Covid-19 was announced in Indonesia. The data consists of stock prices at the end of January 2020 (30 days before the announcement of covid-19) and stock prices at the end of March 2020 (30 days after the announcement of covid-19) for all company sectors on the IDX. The method used is descriptive quantitative. The analysis technique in this study consists of descriptive statistics and hypothesis testing using the nonparametric MANOVA method on the STATCAL software. The results showed that there was a significant difference in stock prices before and after the announcement of the first case of covid-19 in Indonesia, indicated by a significant value per company sector in all sectors <0.05. The value of the permutation test p-value is 0.01, i.e. < 0.05 significance level, it can be concluded that overall, there is a significant difference in stock prices 30 days before and after the announcement of COVID-19, based on 9 company sectors and all company sectors